Subcritical carbon dioxide fluid extraction, isolation and identification of bioactive compounds from Clinacanthus nutans stem - Alam, Md. Ariful (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2017)
Clinacanthus nutans Lindau is one of the species of Acanthaceae family widely known as snake grass. Subcritical Soxhlets carbon dioxide (CO2SOX) extraction has been used for the extraction of bioactive compounds from C. nutans. Two level full factorial design (2k) was applied to identify and optimize the factors- particle size and co-solvent affecting yield, antioxidant activity, total phenolic content (TPC), total flavonoid content (TFC) and α-glucosidase inhibitory activity (AGI) of extracts. Co-solvent was the influential parameter to increase the yield and TPC whereas particle size had a leading effect on TFC, antioxidant and AGI. For optimal results extraction parameters should be set at 90 µm particle size and 300 mL proportionate (3:2) volume of ethanol and water. Most potential optimized extracts (CO2SOX-1-4) from subcritical CO2 Soxhlets extraction were further evaluated for ferric reducing antioxidant power (FRAP), xanthine oxidase inhibitory activity (XOI) and anti-hemolytic activity (AHA). The highest DPPH, XOI and AHA being resulted for 98.90±0.02%, 75.15±4.48 and 46.17±2.53 % for CO2SOX-2. While potential FRAP and AGI observed for CO2SOX-3 (160.33±6.72 µg Ascorbic acid equivalent AAE/g) and CO2SOX-1 (95.66±3.60 %). The TPC significantly (p <0.05) correlated with DPPH and AGI for CO2SOX-1 and CO2SOX-3. Whereas TFC was the most potent for DPPH for all the extracts. Highest DPPH scavenging activity was found for ethyl acetate fraction (79.98±0.31) %. Methanol extract was the most prominent in case of FRAP (141.89±0.87 µg AAE/g). All the extract and fractions exhibited mild to moderate XOI and AHA. The highest AGI resulted for butanol fraction (72.16±1.0) %. In GC-MS based metabolomics, the output OPLS+ t[1] score plot showed a distinct separation into different clusters indicates the variations of samples showed significant activity. After integration of GC-MS data with the observed parameters, significant metabolites effects AGI were identified. A new ubiquinone derivative has been isolated and identified from the C. nutans through UV, FT-IR, LC-MS-MS, 1D NMR (1H, 13C) and 2D NMR (COSY, HMBC) at 500 MHz. The isolated compound showed only a 40.17 % inhibition of the α-glucosidase enzyme. The LC Q-TOF MS analysis proved that CO2SOX extraction selectively separate quinones, phenols and flavonoids from C. nutans. Average lowest toxicity found for CO2SOX extract (26.98%), hexane (23.81%) and residual aqueous fraction (22.22%) thus can be used as chemotherapeutic agents.